Application of Liquid Organic Fertilizer (Bio-fertilizer) Enriched Consortium Bacteria and Golden Snail (Pamoacea canliculata) in Ciherang Rice Flowering - Agus Setiawan; Maria Bintang; Syamsul Falah (IPB University, 2016)
Application of organic fertilizer today has become a necessity, benefits can be felt by farmers using organic fertilizers because increasing content of organic matter and soil nutrition so that increased productivity of agricultural land. Golden snail (Pomacea canaliculata) was introduced to Asia in the 1980s from South America as a potential food for humans. nutritional content of golden snails when added to other ingredients can be a good growth medium for growth of various types of bacteria (consortium) as basic ingredients of liquid organic fertilizer (Bio-fertilizer). Bio-fertilizer was made from golden snail plus consortium bacteria which then carried out isolation and calculation number of bacterial colonies that grow, test activity of phosphate solvent, nitrogen fixation and effectiveness of Ciherang rice flowering. Bio-fertilizer applications made in combination with solid organic fertilizers significantly increase plant height, number of tillers, multiply and accelerate flowering of Ciherang rice.